2015
DOI: 10.1678/rheology.42.309
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of SPH Method for Simulating Gas Bubbles Rising in Viscoelastic Liquids

Abstract: The upward motion and deformation of a single large-scale two-dimensional planar gas bubble rising in an otherwise quiescent viscoelastic liquid obeying the Oldroyd-B rheological model is numerically investigated using the weakly-compressible smoothed particle hydrodynamics (WC-SPH) method. It is shown that unlike the incompressible version of this mesh-less method (I-SPH), the WC-SPH method combined with the continuum surface force (CSF) idea for modelling surface tension is well capable of capturing the cusp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Following these authors, the values of the nondimensional parameters are R e = 1.419, E o = 35.28, W i = 8.083, B i = 0, β = 0.07, k ρ = 0.1, k μ = 0.1, and χ = 0.3. The droplet interface shapes that we obtained at t = 0.13 s together with the ones by Zainali et al and Vahabi and Sadeghy are depicted in Figure . It can be seen in the figure that the present result is consistent with the one reported by Vahabi and Sadeghy; on the contrary, Zainali et al have not observed the cusped trailing edge, which is however a common feature for the case of Newtonian droplet in viscoelastic medium at high polymer concentrations …”
Section: Validationsupporting
confidence: 52%
See 4 more Smart Citations
“…Following these authors, the values of the nondimensional parameters are R e = 1.419, E o = 35.28, W i = 8.083, B i = 0, β = 0.07, k ρ = 0.1, k μ = 0.1, and χ = 0.3. The droplet interface shapes that we obtained at t = 0.13 s together with the ones by Zainali et al and Vahabi and Sadeghy are depicted in Figure . It can be seen in the figure that the present result is consistent with the one reported by Vahabi and Sadeghy; on the contrary, Zainali et al have not observed the cusped trailing edge, which is however a common feature for the case of Newtonian droplet in viscoelastic medium at high polymer concentrations …”
Section: Validationsupporting
confidence: 52%
“…Shape of a Newtonian droplet rising in an Oldroyd‐B fluid at t = 0.13 s. The present results (∘) are compared with the results of Zainali et al (×) and the results of Vahabi and Sadeghy (▿). ( R e = 1.419, E o = 35.28, W i = 8.083, B i = 0, β = 0.07, k ρ = 0.1, k μ = 0.1, χ = 0.3, with 120 × 240 grid points) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Validationmentioning
confidence: 51%
See 3 more Smart Citations